Association of maternal homocysteine and vitamins status with the risk of neural tube defects in Tunisia: A case–control study. Issue 12 (17th August 2015) - Nasri, Kaouther; Ben Fradj, Mohamed Kacem; Touati, Asma; Aloui, Mariem; Ben Jemaa, Nadia; Masmoudi, Aida; Elmay, Michèle Véronique; Omar, Souhail; Feki, Moncef; Kaabechi, Naziha; Marrakchi, Raja; Gaigi, Soumeya Siala
Abstract : Background: This study was conducted to determine whether low folate and vitamin B12 levels, as well as high homocysteine levels in pregnant women are associated with neural tube defects (NTDs) in Tunisia. Methods: A total of 75 NTDs pregnancies and 75 matched controls were included in the study. Their vitamin B12, folate, and red blood cell folate concentrations were measured using a radio‐immunoassay kit and total homocysteine concentrations were determined using a fluorescent polarization immunoassay. Results: Vitamin B12 and folate concentrations were lower in NTD‐affected pregnant women than in controls (respectively, p = 0.009 and p < 0.001). Total homocysteine concentration was significantly higher in the NTDs group than in controls ( p = 0.008). In the case group, the folate levels were positively related with vitamin B12 levels (r = 0.54; p < 0.001) and negatively correlated with total homocysteine levels (r = ‐0.19; p = 0.04). Besides, red blood cell folate levels were positively correlated with folate levels (r = 0.24; p = 0.02) and negatively correlated with total homocysteine levels (r = ‐0.37; p = 0.001). Conclusion: Lower concentrations of folate and vitamin B12 are related to the increased risk of NTDs. Both folate and vitamin B12 intake insufficiency could contribute to the increased risk of NTDs. A dietary supplement, combining folate and vitamin B12, might be an effective measure to decrease the NTDs incidence in Tunisia. Birth Defects Research (Part A) 103:1011–1020, 2015. © 2015 Wiley Periodicals, Inc.